Use trig identities to transform the left side of the equation to the right side.
(1+sintheta)(1-sintheta)=cos2theta
PLEASE HELP ME!!! I WILL MEDAL!

Respuesta :

Answer and explanation

(1+sinθ)(1-sinθ)=cos²θ

We are to prove that the left hand side is equal to the right hand side.

(1+sinθ)(1-sinθ) = 1(1-sinθ) + sinθ(1-sinθ)

                         = 1 - sinθ + sinθ - sin²θ

                          = 1 - sin²θ

From the trigonometric identity sin²θ + cos²θ = 1,

1 - sin²θ = cos²θ


ACCESS MORE